Digital Marketing Strategy For Acnes Skincare Products - Martinus Edwin Thanos; Carl C. G. Dizon (Ultimacomm: Jurnal Ilmu Komunikasi, 2023)
Along with the development of the era, technology has changed marketing strategies. Marketing using digital-based social media makes it easier for businesses to introduce products to increase sales. The use of digital marketing has advantages over traditional media. Acnes, through its Instagram account, conduct marketing with various strategies. This research uses Krippendorff's content analysis method on content uploads from January 1, 2023, to March 31, 2023. The conclusion of this research is that @acnesid focuses on sales promotion so that customers continue to purchase skin care products.